The genetic and genomic background of methane emission and feed efficiency in dairy cattle - Breider, Irene Susanne (2018)
One of the biggest challenges facing modern society is climate change. Greenhouse gases, including methane (CH4), play an important role in global warming. Dairy cattle produce 20% of global livestock sector emissions and reducing their impact will have an important influence on total CH4 production. Few genetic parameters for enteric CH4 production are currently available. This study obtained parameters for CH4 production and milk yield (MY), life weight (LWT) and dry matter intake (DMI) for three research populations. Heritabilities, repeatabilities, genetic, and phenotypic correlations were obtained using restricted maximum likelihood models. Selection index theory was used to investigate the effect of including CH4 production in national breeding goals of three European countries, under different scenarios. Life cycle assessment was performed to investigate change in CH4 production for the whole sector when CH4 related traits (calving index, lactation number, LWT, feed intake and MY) increased. Heritabilities derived for CH4 production using pedigree based analyses varied from 0.03 to 0.45. Genetic correlations derived between CH4 production and MY, LWT and DMI varied from -0.36 to 0.57, 0.00 to 1.10 and 0.05 to 0.98 respectively. Including CH4 production in national breeding goals showed that CH4 production is currently increasing. Imposing a restriction or economic value on CH4 production reduced, but did not completely eradicate, the increase in genetic gain. Life cycle assessment showed a decrease in CH4 production lost to air when increasing CH4 related traits, except for live weight, which caused an increase. In conclusion, it is possible to genetically select cows for lower CH4 production. Including CH4 production in the national breeding goal but restricting CH4 production results in a decrease in genetic gain but does not eradicate CH4 production. Eradication of CH4 production through genetics was not the goal of this study. Life cycle assessment analysis showed the importance of focus on sector level rather than cow level when reducing CH4 production within the dairy sector.